2019
DOI: 10.1002/pssa.201800889
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and Optical Properties of (Cu1−xLix)2SnS3 Photovoltaic Semiconductor

Abstract: In order to clarify a lack of knowledge on lithium alloying with Cu2SnS3 (CTS), the authors synthesized monoclinic (Cu1–xLix)2SnS3 with 0.0 ≤ x ≤ 0.10 and characterized their crystallographic and optical properties. Their lattice constants, a, b, and c increased and angle β decreased with increasing Li content. Two band‐gaps (Eg1 and Eg2) are observed for the (Cu1–xLix)2SnS3 samples because there is a double onset in the diffuse reflectance spectra. The Eg1 almost linearly increases from 0.91 eV for x = Li/(Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Figure a,b consequently demonstrates PYS spectra of the CIGSSe absorbers on flexible SUS substrates without and with air‐annealing process at 130 °C for 6 h. It is revealed in Figure 5a that near‐surface region of the CIGSSe absorber without the air‐annealing process, having small Ga content near CIGSSe surface, [ 39–41 ] is composed of CIGSSe and In 2 S 3 with E V values of about −5.2 and −6.1 eV, respectively. It has been reported that E V values of CuInSe 2 and CuInS 2 are about −5.2 and −5.5 eV, [ 42,43 ] as well as that of In 2 S 3 is in a range from about −6.0 to −6.2 eV. [ 44,45 ] In addition, the different E V between CIGSSe and In 2 S 3 (Δ E V ) is 0.9 eV in Figure 5a.…”
Section: Resultsmentioning
confidence: 98%
“…Figure a,b consequently demonstrates PYS spectra of the CIGSSe absorbers on flexible SUS substrates without and with air‐annealing process at 130 °C for 6 h. It is revealed in Figure 5a that near‐surface region of the CIGSSe absorber without the air‐annealing process, having small Ga content near CIGSSe surface, [ 39–41 ] is composed of CIGSSe and In 2 S 3 with E V values of about −5.2 and −6.1 eV, respectively. It has been reported that E V values of CuInSe 2 and CuInS 2 are about −5.2 and −5.5 eV, [ 42,43 ] as well as that of In 2 S 3 is in a range from about −6.0 to −6.2 eV. [ 44,45 ] In addition, the different E V between CIGSSe and In 2 S 3 (Δ E V ) is 0.9 eV in Figure 5a.…”
Section: Resultsmentioning
confidence: 98%
“…In Figure 1b,c the energy level diagram of FTO/ZnO/meso‐ Bi 2 Se 3 or CuInSe 2 : MAPbI 3 /Spiro_OMeTAD/Au configuration are shown. [41–43] The most important characteristic of ETL is its role in band alignment with the perovskite layer [44]. The energy level of CuInSe 2 is well‐aligned with other layers (CH 3 NH 3 PbI 3 and ZnO with a band‐gap of 3.44 eV [26, 45]), which lowers the driving force needed for electron injection from MAPbI 3 to CuInSe 2 [12].…”
Section: Model Descriptionmentioning
confidence: 99%
“…In Figure 1b,c the energy level diagram of FTO/ZnO/meso-Bi 2 Se 3 or CuInSe 2 : MAPbI 3 /Spiro_OMeTAD/Au configuration are shown. [41][42][43] The most important characteristic of ETL is its role in band alignment with the perovskite layer [44].…”
mentioning
confidence: 99%